(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Soil-transmitted helminths (STHs) are included in the listof the world’s neglected tropical diseases. The STHs include the roundworm Ascaris lumbricoides, the whipworm Trichuris trichiura, the hookworms, Ancylostoma duodenale and Necator americanus, and Strongyloides stercoralis. The study was aimed to determine parents/car-givers of under-five children’s knowledge, attitudes and practices towards STHs in Taraba State, Nigeria. STHs infection is among the most chronic diseases globally. Because of its impact on human health, the WHO recommended the carrying out of robust approaches targeted at controlling or eliminating disease. The execution of this approach depends on the vivid understanding of the parent’s/caregivers’ knowledge, attitudes and practices in relation to this infection. A cross-sectional survey was conducted and data were assembled with the aid of a standardized questionnaires from 2,283 caregivers of under-five children. Extensive focus group discussions were carried out among parents/caregivers and the collected data were analysed thematically. Out of the six selected LGAs in Taraba State, highest albendazole coverage of 193(50.79%) was recorded in Bali LGA and least (47.89%) was recorded in Jalingo LGA. More so, a total STH prevalence of 3.29% was recorded among under-5 children who were dewormed six months ago before the survey period and 12.52% was also recorded among under-5 children who were not dewormed. Findings from this study also reflected adequate knowledge and attitudes with bad practices in connection to STHs among parents/caregivers while recognition of soil-transmitted helminths was high (94.2%). These reports are important in planning behavioural change approaches towards improving health results across community-based involvement...